South Florida Tropicals: Carambola - Amy Simonne; Linda Bobroff (EDIS)
The carambola or star fruit is native to Southeast Asia. It was introduced to Florida about 100 years ago. This 4-page fact sheet is a major revision that discusses availability, selection, uses, nutritive value, and food safety during preparation of carambola. This document also includes several recipes.